A INVISIBILIDAE DO ESSENCIAL: ECONOMIA DO CUIDADO E AS DESIGUALDADES ESTRUTURAIS - CHAGAS, DANIEL HEDLUND SOARES DAS; SILVEIRA, DANIEL CLAUDY DA; NOGUEIRA, SANDRA VIDAL; OLIVEIRA, TARCISIO DORN DE (Salão do Conhecimento, 2025)
A INVISIBILIDAE DO ESSENCIAL: ECONOMIA DO CUIDADO E AS DESIGUALDADES ESTRUTURAIS